Editorial - Capogna, Stefania; Šimanskienė, Ligita; Župerkienė, Erika (Community Notebook. People, Education and Welfare in the Society 5.0, 2024)
In the ever-evolving realm of higher education, where the pervasive influence of digitalization is reshaping traditional paradigms, we are pleased to present this special issue of the Journal Quaderni di Comunità. Titled Reinventing University. The Digital Challenge In Higher Education , this collection of papers navigates the multifaceted intersections between technology and higher education, offering a timely exploration of the challenges and opportunities that define the contemporary academic landscape. The digital challenge in higher education is not merely a technological shift but a transformative force reshaping the essence of academic practices. As we stand at the confluence of tradition and innovation, this special issue serves as a repository of insights, ideas, and innovations, each carefully curated by the D-ChallengHE Scientific Board, as part of the second work package addressed to promote the D-ChallengHE Hub Research Network (Project Code: 2022-1-IT02-KA220-HED-000087029). These contributions delve into the complexities of reinventing universities in the digital age, addressing the critical themes that resonate across the academic spectrum.